Notes on type specimens of Rhinogobius flumineus (Mizuno 1960) (Perciformes: Gobiidae) and Cobitis takatsuensis Mizuno 1970 (Cypriniformes: Cobitidae) in Tokushima Prefectural Museum, Tokushima, Japan - Ito, Taiki; Suzawa, Yuzuru; Sato, Yoichi (Zootaxa, 2024)
Rhinogobius flumineus and Cobitis takatsuensis were described as new species by Prof. Nobuhiko Mizuno in 1960 and 1970, respectively. Within the manuscripts, he mentioned that he had preserved the type specimens of these species in his private collection. Professor Mizuno concluded his tenure at Ehime University, Japan, in 1996, and subsequently, Tokushima Prefectural Museum (TKPM) received his collection, which included the type specimens of R. flumineus and C. takatsuensis. However, the whereabouts of his collection is not widely known. Here we provide detailed notes of the holotypes and paratypes of R. flumineus and C. takatsuensis housed in TKPM. The information presented herein will contribute to future taxonomic investigations of East Asian freshwater fishes.